Korelasi Hasil dan Komponen Hasil Padi Hibrida di Dua Lokasi Pengujian - Kartina, Nita (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
One of the objectives in rice breeding is to increase grain yield. The research was to evaluate numbers of hybrid rice genotypes and also to obtain the information about grain yield correlation main, grain yield component from numbers of hybrid rice genotypes and influencial character as selection criteria. The experiment conducted in the second season (MT II) of 2013 at Cilacap, Central Java province and in Malang, East Java province by using Randomized Complete Block Design (RCBD) with four replications. The genetic materials used were 18 hybrid rice genotypes and two check varieties namely Hipa8 and Ciherang. The results showed that grain yield had been effected by location, genotypes and both interactions. Hipa8 give yield average 9 t/ha while Ciherang 8.78 t/ha. There were two hybrid rice genotypes have equal yield statitistically with both check varieties. The hybrids were A7/BH25B-1B(9.13 t/ha) and IR58025A/CRS516 (9.15 t/ha). Based on path analysis numbers of empty grain, seed set, plant high and number of productive tillers have direct effect to yield with path coefficient of 0.0437; 0.3114; 0.,1952 and 1.931.These characters could be used as selection criteria.